Moral hazard resolved by common-knowledge in principal-agent model. (1st January 2012) - Matsuhisa, Takashi
This paper investigates the role of common-knowledge in the principal-agent model under uncertainty. We treat the problem: How epistemic conditions will be able to settle a moral hazard in team in the principal-agent model under uncertainty. We shall propose a resolution programme for the moral hazard in the principal-agent model by common-knowledge. Let us assume that the agents have the knowledge structure induced from a binary relation associated with the multi-modal logic S5n or S4n . We show that the moral hazard can be resolved in the principal-agent model under uncertainty if the agents commonly know all their own costs.